Ecological Predictors and Functional Implications of Eye Size in Deep-Sea Shrimps - Schweikert, Lorian E.; Thomas, Kate N.; Moreno, Vanessa M.; Casaubon, Anchita; Golightly, Charles; Bracken-Grissom, Heather D. (Frontiers in Ecology and Evolution, 2022)
Constraints on energy resources and available light in the deep sea should place strong selection pressure on eye size, a fundamental determinant of visual ability. By examining eye size among 16 species (454 individuals) of deep-sea sergestid shrimps, we show significant differences in intraspecific eye growth rates and species eye-size averages that are correlated to different aspects of ecology and result in variable sighting distance thresholds of bioluminescence, one measure of visual performance. We used linear regressions modeling the lowest and highest bounds of phylogenetic signal to test for ecological correlates of relative and absolute eye size, which indicate the allocation of energetic resources toward eyes and an optical basis of visual capability, respectively. Of the ecological variables tested (mean depth, diel vertical migration (DVM) distance, habitat type, and light organ type), light organ type was the only significant correlate of both relative and absolute eye size, suggesting that sergestids rely on bioluminescent signaling. Our findings also suggest that the DVM imposes visual demands distinct from the average depths occupied by a species. While DVM distance correlated with relative eye size, mean depth correlated with absolute eye size, revealing that eye size increases with depth before 1000 m, then decreases in bathypelagic (aphotic) zone. By applying measured eye sizes to models of visual performance, we estimated that sergestids can detect a bioluminescent point source from ≤3.77 m away, and that these sighting distance thresholds vary between species by a factor of three. In relative terms, however, all sergestids under the test conditions had a common detection threshold at 63.5 body lengths, suggesting that bioluminescence sighting distance is proportional among species and may be related to shared behaviors of swarming and copulation. By considering the effects of evolutionary history, light and nutrient availability, and the constraints of body size, our study reveals new patterns of deep-sea eye size evolution and provides new insights into the visual ecology of this diverse and important deep-sea group.